Susceptibility Profile of Pseudomonas Aeruginosa to Amikacin and Imipenim by Disc Diffusion and Minimum Inhibitory concentration Method - Iqbal, Mehveen (International Journal of Pathology, 2022)
Background: The resistant strains of Pseudomonas aeruginosa become life threatening if not treated promptly. The objective of the study was to determine the susceptibility pattern of Pseudomonas aeruginosa to amikacin and imipenem by Disc diffusion and Minimum Inhibitory Concentration method. Materials &Method: This cross sectional study was conducted from December 2019 to December 2020 at Creek general hospital and Zubaida medical center, Karachi. Samples of pus, blood and tracheal aspirates were collected. Samples were streaked on blood and Mac Conkey`s agar and further confirmed by API 20 NE system. Antimicrobial susceptibility of amikacin and imipenem was performed by Kirby- Bauer disk diffusion method and Minimum inhibitory concentration testing method. SPSS version 22.0 was used for statistical analysis Results: A total of 200 samples were collected. Out of 200, 64 (32%) positive samplesre further analyzed. 60.9 % (n=39) strains were isolated from pus. 64 positive samples ere tested for antimicrobial susceptibility of amikacin and imipenem by disc diffusion and minimum inhibitory concentration method. Out of 64, 82.8% (n=53) of isolates were observed resistant to amikacin by disc diffusion method followed by 62.5% (n=40) by minimum inhibitory concentration method. Intermediate sensitivity of amikacin was observed 28.12% (n=18) by minimum inhibitory concentration. 67.18% (n=43) isolates showed resistance to imipenem with minimum inhibitory concentration method as compared to 53.98% (n=34) resistant isolates when tested with disc diffusion method Conclusions: Two testing methods should be used in-conjunction to determine susceptibility of antimicrobials to assess the correct burden of resistant isolates of Pseudomonas aeruginosa